KEPASTIAN HUKUM TENTANG PENGAKTIFAN KEMBALI PRAJURIT TNI BERDASARKAN PUTUSAN PENINJAUAN KEMBALI MAHKAMAH AGUNG REPUBLIK INDONESIA TERHADAP PENIADAAN PIDANA TAMBAHAN PEMECATAN - Ahmad Jaeni; Maliki Setyawan; Hedwig Adianto Mau; Rudy M Ramdan (Journal of Social, Humanity, and Education, 2026)
Purpose: This study examines the legal implications of the dismissal of Indonesian National Armed Forces (TNI) soldiers, particularly when a Military Court's review decision revokes the dismissal penalty. It explores whether soldiers, once dismissed for legal violations, should be entitled to reinstatement if the dismissal penalty is nullified. Research Methodology: The research uses a qualitative approach with document studies and interviews. Document studies analyze legal documents, court rulings, and administrative regulations, while interviews involve legal experts, TNI personnel, and stakeholders in military law. Results: The findings suggest that the revocation of the dismissal penalty in a review decision can be considered a novum (new legal fact), nullifying the legal basis for the dismissal. As a result, the dismissal becomes invalid, and the soldier may be entitled to apply for reinstatement in the military. Conclusions: The study concludes that soldiers whose dismissals are revoked in a review decision should have the right to seek reinstatement. However, current regulations do not provide for such a provision, highlighting the need for regulatory changes to accommodate this right. Limitations: The study is limited by the availability of relevant legal cases and the absence of administrative regulations on reinstating dismissed soldiers. Further research may be needed to explore broader implications for TNI personnel. Contributions: This research contributes to the understanding of legal processes regarding military personnel, offering recommendations for policy reforms in military justice and personnel management.